IDEAL Model Education to Increase Knowledge and Self-Care Practices for People with HIV/AIDS (PLWHA): Quasi-Experimental Study - Mentari Chrystiani Lasi; Kuswantoro Rusca Putra; Dina Dewi Sartika Lestari Ismail (Universitas Aisyah Pringsewu, 2023)
People with HIV/AIDS (PLWHA) often have problems with self-care processes due to a lack of knowledge and support from those around them. Education development is needed with the IDEAL model (Include, Discuss, Educate, Assess, Listen), which aims to ensure the continuity of the independent care process at home that PLHIVs carries out with their families. This study aims to determine the effect of providing IDEAL model education on increasing knowledge and self-care practices of people living with HIV/AIDS. The study used a quasi-experiment with a non-equivalent control group using a purposive sampling technique with a total sample of 46 respondents. The results of the t-test in the experimental group's level of knowledge were p-value = 0.000 and self-care p-value = 0.0001 (less than 0.005); the meaning was an effect before and after giving the intervention. The Manova test results obtained a p-value of 0.133 (more than 0.005), meaning interventions. That there was no difference. Educational development using the IDEAL model has been proven to increase the knowledge, abilities, and self-care skills of PLWHA. Abstrak: Orang Dengan HIV/AIDS (ODHA) sering memiliki masalah dengan proses perawatan diri akibat kurangnya pengetahuan dan dukungan dari orang-orang di sekitarnya. Dibutuhkan pengembangan Edukasi dengan model IDEAL (Include, Discuss, Educate, Assess, Listen) yang bertujuan untuk memastikan kesinambungan proses perawatan secara mandiri di rumah yang dilakukan ODHA bersama keluarga. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian edukasi model IDEAL terhadap peningkatan pengetahuan dan praktik perawatan diri orang dengan HIV/AIDS. Penelitian menggunakan quasi-experiment dengan non-equivalent control group menggunakan teknik purposive sampling dengan jumlah sampel 46 responden yang menjalani. Hasil uji t-test pada kelompok eksperimen tingkat pengetahuan p-value 0,000 dan perawatan diri p-value = 0.0001 (kurang dari 0.005), artinya ada pengaruh sebelum dan sesudah diberikan intervensi. Hasil uji Manova didapatkan hasil p-value = 0.133 (lebih dari 0.005), artinya tidak ada perbedaan tingkat pengetahuan dan praktik perawatan diri pada kedua kelompok. Pengembangan edukasi dengan model IDEAL terbukti dapat meningkatkan pengetahuan, kemampuan, dan keterampilan perawatan diri ODHA.